Evaluation of anti anxiety activity of Datura seeds in mice - Alka Tiwari, Alka Tiwari; Jagdish Rathi, Jagdish Rathi; Sandeep Kumar Dwivedi, Sandeep Kumar Dwivedi; Sanno, Sanno; Saurab Tripathi, Saurab Tripathi (International Journal of Indigenous Herbs and Drugs, 2018)
Objective: The aim of the present work was to evaluate the anti-anxiety activity of ethanolic extract of Datura stramonium (leaves).Methods: Elevated plus-maze apparatus were used for finding anti-anxiety activity of the ethanolic extract of Datura stramonium (leaves). Pre-treated animals were placed individually for 5 min in the maze. The number of entries into the open and closed arm, time spent in each arm and the number of entries in both the arms was noted.Results: The result showed that the ethanolic extract of leaves of Datura stramonium (100 and 200 mg/kg) and diazepam (1 mg/kg) induced significantly (P<0.01) increase in the occupancy in the open arm and showed a decrease preference for the closed arm entries.Conclusion: Administration of ethanolic extract of leaves of Datura stramonium (100 and 200 mg/kg) possessed significant antiaxiety effects as compared to control.